2012
DOI: 10.1073/pnas.1203720109
|View full text |Cite
|
Sign up to set email alerts
|

Gas-liquid transfer data used to analyze hydrophobic hydration and find the nature of the Kauzmann-Tanford hydrophobic factor

Abstract: Hydrophobic free energy for protein folding is currently measured by liquid-liquid transfer, based on an analogy between the folding process and the transfer of a nonpolar solute from water into a reference solvent. The second part of the analogy (transfer into a nonaqueous solvent) is dubious and has been justified by arguing that transfer out of water probably contributes the major part of the free energy change. This assumption is wrong: transfer out of water contributes no more than half the total, often l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…Chandler [28,29] argued persuasively, however, that the cavity work in water is not proportional to surface area in the small-size regime (see below) but instead scales linearly with molar volume. Until now, the controversy has been based on data for liquid-liquid transfer, which is more complex than gas-liquid transfer because DG LL depends on the values of DG c and E a in both liquid alkane and water [5].…”
Section: The Cavity Work Scales With Molar Volumementioning
confidence: 99%
See 4 more Smart Citations
“…Chandler [28,29] argued persuasively, however, that the cavity work in water is not proportional to surface area in the small-size regime (see below) but instead scales linearly with molar volume. Until now, the controversy has been based on data for liquid-liquid transfer, which is more complex than gas-liquid transfer because DG LL depends on the values of DG c and E a in both liquid alkane and water [5].…”
Section: The Cavity Work Scales With Molar Volumementioning
confidence: 99%
“…1 to plot DG c (water) against molar volume (V) for 4 linear alkanes. McAuliffe [12] showed that a plot of this kind should be limited to hydrocarbons of a single type, such as linear or cyclic, because [4] (see [5]). DG GL is the sum of E a and DG c .…”
Section: The Cavity Work Scales With Molar Volumementioning
confidence: 99%
See 3 more Smart Citations